Profile of consumers of Popular Restaurant in the center region of the Rio Grande do Sul state - Souza, Fábio Roberto de; Dörr, Andrea Cristina; Saldanha, Patrick Gonçalves; Tonetto, Thaíse da Silva; Guse, Jaqueline Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The aim of this study is to analyze the profile of consumers of the popular restaurant Dom Ivo Lorscheiter (RPDIL) located in Santa Maria - RS. Primary data were obtained through a structured questionnaire applied to 165 consumers in the restaurant during the period of 17 to 20 June 2013. The results show that most consumers are male, unmarried and aged between 16-25 years and above 56 years. Have a monthly average income between 1 and 1,5 minimum wages and are willing to pay R 5,00 per meal at another restaurant. We conclude that the popular restaurant meets its social role as anyone in the population may have access to subsidized meals. Moreover, the monetary benefit generated daily by the restaurant to the consumers totalized R 1,593.75, which may be appropriated by the consumers in the form of welfare and health.